Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/1615-9314(20021101)25:15/17<1155::aid-jssc1155>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study on the opposite migration order of the enantiomers of ketamine with α- and β-cyclodextrin in capillary electrophoresis

Abstract: The enantiomer migration order of the chiral anaesthetic drug ketamine [RS‐2‐(2‐chlorophenyl)‐2‐(methylamino)cyclohexanone] was studied by capillary electrophoresis using various cyclodextrins as chiral selectors. The opposite migration order of the enantiomers of ketamine was observed when native α‐ and β‐cyclodextrins were used as chiral selectors in capillary electrophoresis. The possible mechanisms of the opposite enantiomer migration order were investigated by employing electrospray ionization mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 48 publications
6
50
0
Order By: Relevance
“…There are different ways to change the enantiomeric migration order by CE when CDs are used as chiral selectors [4,[10][11][12][13]: (i) modifying the CD cavity size [14]; (ii) changing the nature of CD substituents [15,16]; (iii) varying the location of substituents on the CD rim [17]; (iv) employing charged CDs in the BGE and changing the polarity of the applied voltage [18,19]; (v) modifying the pH of the BGE [18,20]; (vi) changing the EOF, i.e., eliminating or reversing it [19,20]; (vii) using achiral additives (i.e., micelles or ligandexchange compounds as metals) in chiral systems [21,22], and finally, (viii) varying the concentration of the CD in the separation buffer. However, this last phenomenon has scarcely been observed.…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways to change the enantiomeric migration order by CE when CDs are used as chiral selectors [4,[10][11][12][13]: (i) modifying the CD cavity size [14]; (ii) changing the nature of CD substituents [15,16]; (iii) varying the location of substituents on the CD rim [17]; (iv) employing charged CDs in the BGE and changing the polarity of the applied voltage [18,19]; (v) modifying the pH of the BGE [18,20]; (vi) changing the EOF, i.e., eliminating or reversing it [19,20]; (vii) using achiral additives (i.e., micelles or ligandexchange compounds as metals) in chiral systems [21,22], and finally, (viii) varying the concentration of the CD in the separation buffer. However, this last phenomenon has scarcely been observed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was used to explain the opposite migration order of the ketamine enantiomers in the presence of a-CD and b-CD [61]. NMR studies indicated a deeper inclusion of ketamine into the cavity of b-CD compared to a-CD.…”
Section: Separation Of Drug Enantiomersmentioning
confidence: 99%
“…The affinity pattern of GT enantiomers towards these two CDs was the same. Interestingly, the affinity pattern of the enantiomers of aminoglutethimide was opposite towards native a-and b-CD [5]. From single-component charged b-CD derivatives, HMdiSu-b-CD containing 14 sulfate groups did not attain the enantioseparation while all other randomly and selectively substituted charged b-CD derivatives afforded enantioseparation.…”
Section: Enantioseparation Of Gt In Cementioning
confidence: 99%
“…In addition, CE enables to study fine nuances of intermolecular interactions in solution, which are hardly accessible by other techniques [4][5][6]. Several important advantages of CE facilitate its application for the latter purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation